Developing a Humanistic Counseling-Based Framework to Enhance Students’ Academic Well-Being in the Merdeka Curriculum Context - Salsabila, Nur Nafisa; Qiptiah, Devi Mariatul (FKIP Universitas Islam Jember, 2025)
This study aims to develop a humanistic counseling framework that is contextually aligned with the dynamics of the Merdeka Curriculum, particularly concerning the phenomena of autonomy overload, self-regulation pressure, and students’ emotional uncertainty. The research employed a qualitative method with a phenomenological approach through in-depth interviews, participatory observations, and school document analysis. The data were analyzed thematically using open coding, axial coding, and selective coding to produce a comprehensive theoretical construction. The findings indicate that the principles of humanistic counseling possess relational capacities that directly address the mechanistic challenges emerging within autonomy-based learning. This theoretical and empirical synthesis yields three core dimensions of the framework: Empathic-Autonomy Alignment, Academic Self-Actualization Support, and Reflective-Experiential Guidance. These dimensions work interdependently to strengthen healthy autonomy, enhance academic clarity, and stabilize students’ emotional well-being. The study offers a conceptual contribution to the development of school counseling models that are relevant to the needs of contemporary education in Indonesia.